Digitization of Library Materials - Adzic, Aleksandra (Infotheca - Journal for Digital Humanities; Vol 14 No 1 (2013): Infotheca - Journal of Informatics and Librarianship, 2024)
Libraries are important centers for creating information. The improvement of their services is based on opportunities provided by the rapid development of information and communication technologies. The process of creating a digital library is one of the responses to the demands of users who want to find information in the manner of today. Specifically, we are not talking about new data, but a radical improvement of the way in which data are made available to end users, with respect to time as the only category that is absolutely irreversible in the process of creating information. Digitization of library materials is a very complex process, regardless of all the technical equipment an institution has at its disposal. Communicating with colleagues about the problems that occur during the initial phases in creating a digital library, difficulties appearing because of the many recommendations and guidelines in this area, the need to detect crucial aspects during the implementation of the digitization process – all of these require to be presented in one place and in an understandable way with possible solutions resulting from practice.